2011
DOI: 10.1177/0907568211413941
|View full text |Cite
|
Sign up to set email alerts
|

Contexts of childhood and play: Exploring parental perceptions

Abstract: The article explores cross-cultural notions of play in childhood among parents based on empirical investigations in two economically diverse residential areas in a metropolis in India. All parents had an unquestionable belief in an epistemic grounding of play in children's lives. However, parents begin to question play timings and children's engagement with play when faced with the contemporary demands of schooling which are enmeshed in a childhood dominated by academic achievement, suppressing parents' intuit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 10 publications
2
20
0
Order By: Relevance
“…Certain parenting practices common among the middle-class are partially responsible for this shift. The prioritization of academic achievement [ 8 , 9 ] and the tendency for middle-class parents to engage in “concerted cultivation”—Enrolling children in an abundance of extra-curricular enrichment activities, has left children with little unstructured time [ 8 , 10 ]. Heightened concerns for child safety ( i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Certain parenting practices common among the middle-class are partially responsible for this shift. The prioritization of academic achievement [ 8 , 9 ] and the tendency for middle-class parents to engage in “concerted cultivation”—Enrolling children in an abundance of extra-curricular enrichment activities, has left children with little unstructured time [ 8 , 10 ]. Heightened concerns for child safety ( i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Our review found some older but relevant studies such as Shah (1991) that addresses the relationship between home and school in the context of academic achievement; Mishra (1992) that discusses the impact of academic achievement on self-concept; and a study by Verma, Sharma and Larson (2002) that provided an insight into the effect of school stress on Indian children and finally, Singh and Sengupta (2010) provide a tool for measuring academic anxiety in children. While we would be discussing this further in this article, a point to confirm is that the expectations of Indian parents of their children's scholastic achievements continue to be the same either in homeland, that is, India or overseas such as UAE, corroborating the stresses the Indian children go through and for which Singh and Gupta (2012) above have called for avenues that equally also divert the child from singular academic focus.…”
Section: The Context Of United Arab Emirates (Uae)mentioning
confidence: 68%
“…With regard to emotional challenges experienced by Indian children, Singh and Gupta (2012) reported positively on the role of play in children’s lives and the diversion from this to an academic focus in a comparative study. Our review found some older but relevant studies such as Shah (1991) that addresses the relationship between home and school in the context of academic achievement; Mishra (1992) that discusses the impact of academic achievement on self-concept; and a study by Verma, Sharma and Larson (2002) that provided an insight into the effect of school stress on Indian children and finally, Singh and Sengupta (2010) provide a tool for measuring academic anxiety in children.…”
Section: The Context Of United Arab Emirates (Uae)mentioning
confidence: 99%
“…Thus, although Mischa's digital art was favoured by her teachers over the artwork of other children, it actually demonstrated the smallest degree of flexibility or 'mash-up' (Lamb, 2007) in its image use. Valuing playfulness is particularly important in the context of emerging digital environments which are often seen as impinging upon play rather than as a resource through which play can occur (Singh & Gupta, 2011;Edwards, 2013).…”
Section: Discussionmentioning
confidence: 99%